The Bin Laden plot - Campbell, Rick (Navy Commander) (Trident deception series, 2024)
"A U.S. destroyer is torpedoed by an Iranian submarine and Captain Murray Wilson of the U.S.S. Michigan is flown to the Pentagon to meet with the Secretary of the Navy (SecNav). There, Wilson learns that the Iranian submarine is just a cover story. One of the United States' own fully automated unmanned underwater vehicles has gone rogue, its programing corrupted in some way. Murray is charged with hunting it down and taking it out before the virus that's infected its operating system can infect the rest of the fleet. At the same time, the head of the SEAL detachment aboard the U.S.S Michigan is killed and Lonnie Mixell, a former U.S. operative, now assassin for hire, is responsible. And that is only the first SEAL to be hunted down and killed. Jake Harrison, fellow SEAL, discovers that these SEALs had one mission in common - they were all on the team that killed Bin Laden. Or so the world was told. As Wilson discovers that his mission is actually meant to cover up dangerous acts of corruption, even treason, Harrison discovers that the assassin is out to protect the same forces. Forces too powerful for either of them to take on alone"--